1992
DOI: 10.1016/0014-5793(92)80506-c
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid composition is different between the cytoplasmic and extracellular sides in membrane proteins

Abstract: The amino acid composition of transmemhrane proteins was analyzed for their three separate portions: the transmembrane apolar, cytoplasmic and extracellular regions. The composition was different between cytoplasmic and extracellular peptides; alanine and argininc residues were preferentially sited on the cytoplasmic side, while the threonine and cysteinc/cysdne were preferentially sited on the extracellular side, The composition ofcytoplasmic and extracellular peptides of membrane protcinscorresponded to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 63 publications
1
23
2
Order By: Relevance
“…More specifically, the extracellular regions are expected to be dominated by residues favoring the β-sheet structure, such as Val, Ile, Phe and Tyr. Interestingly, aromatic residues (Trp, Tyr and Phe) are preferred on the extracellular side of membranes, whereas charged residues, both basic (Arg, Lys) and acidic (Glu, Asp), are preferentially sited on the cytoplasmic side [31]. These results are in accord with previous studies that performed structural predictions and showed that the extracellular domains of BY-kinases from Proteobacteria tend to favor β-structures [6].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…More specifically, the extracellular regions are expected to be dominated by residues favoring the β-sheet structure, such as Val, Ile, Phe and Tyr. Interestingly, aromatic residues (Trp, Tyr and Phe) are preferred on the extracellular side of membranes, whereas charged residues, both basic (Arg, Lys) and acidic (Glu, Asp), are preferentially sited on the cytoplasmic side [31]. These results are in accord with previous studies that performed structural predictions and showed that the extracellular domains of BY-kinases from Proteobacteria tend to favor β-structures [6].…”
Section: Resultssupporting
confidence: 86%
“…The NAKH920103 property is the AA composition of EXT of single-spanning proteins and provides the average amino acid composition of the extracellular regions of single-spanning transmembrane proteins [31]. The SCM-generated amino acid scores, positively correlated ( p  = 0.50) with the NAKH920103 scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that acidic residues are rare even compared to positively charged residues, which are about three to four times more frequent. On a much smaller dataset of single-spanning transmembrane proteins, Nakashima and Nishikawa [51] made similar compositional studies. To compare, they found 0.94% glutamate and 0.94% aspartate within just the TMH region (these values are very similar to ours from TMHs with small flanks; apparently, they used more outwardly defined TMH boundaries), but the content of each glutamate and aspartate within the extracellular or cytoplasmic domains is larger by an order of magnitude, between 5.26% and 9.34%.…”
Section: Resultsmentioning
confidence: 84%
“…The properties are propensity (BLAM930101) [9] (HQI1), information value for accessibility (BIOV880101) [10] (HQI2), normalized frequency of alpha-helix (MAXF760101) [11] (HQI3), volumes including the crystallographic waters (TSAJ990101) [12] (HQI4), amino acid composition of MEM of multi-spanning proteins (NAKH920108) [13] (HQI5), composition of amino acids in intracellular proteins (CEDJ970104) [14] (HQI6), conformational preference for all beta-strand (LIFS790101) [15] (HQI7), and optimized relative partition energies (MIYS990104) [16] (HQI8). HQI features are extracted by representing the amino acid residues surrounding the hydroxylation site by a property of a corresponding index.…”
Section: Methodsmentioning
confidence: 99%